Pengaruh Lingkungan Kerja Non Fisik terhadap Kinerja Karyawan Melalui Komunikasi di PT. Suzuki Indomobil Motor Plant Tambun II - Arief Subagio; Supardi Supardi; Agus Dharmanto (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This study aims to determine whether the Non-Physical Work Environment affects Employee Performance through Communication. The method used in this research is quantitative method. Data analysis using Smart PLS 3.0. The analysis methods used are descriptive analysis, validity test, reliability test, r-square test, q-square test and hypothesis testing. The results showed that the non-physical work environment had a positive and significant effect on communication by 83%. Communication has a positive and significant effect on employee performance by 79%. The non-physical work environment has no effect on employee performance. The non-physical work environment on employee performance through communication has a positive and significant effect of 66.5% and the remaining 33.5% is influenced by other factors.